Three doses of a recombinant conjugated SARS-CoV-2 vaccine early after allogeneic hematopoietic stem cell transplantation: predicting indicators of a high serologic response—a prospective, single-arm study - Barkhordar, Maryam; Chahardouli, Bahram; Biglari, Alireza; Ahmadvand, Mohammad; Bahri, Tanaz; Alaeddini, Farshid; Sharifi Aliabadi, Leyla; Noorani, Seied Saeid; Bagheri Amiri, Fahimeh; Biglari, Mohammad; Shemshadi, Mohammad Reza; Ghavamzadeh, Ardeshir; et al. (Frontiers in Immunology, 2023)
Background Allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients must be vaccinated against SARS-CoV-2 as quickly as possible after transplantation. The difficulty in obtaining recommended SARS-CoV-2 vaccines for allo-HSCT recipients motivated us to utilize an accessible and affordable SARS-CoV-2 vaccine with a recombinant receptor-binding domain (RBD)–tetanus toxoid (TT)-conjugated platform shortly after allo-HSCT in the developing country of Iran. Methods This prospective, single-arm study aimed to investigate immunogenicity and its predictors following a three-dose SARS-CoV-2 RBD–TT-conjugated vaccine regimen administered at 4-week (± 1-week) intervals in patients within 3–12 months post allo-HSCT. An immune status ratio (ISR) was measured at baseline and 4 weeks (± 1 week) after each vaccine dose using a semiquantitative immunoassay. Using the median ISR as a cut-off point for immune response intensity, we performed a logistic regression analysis to determine the predictive impact of several baseline factors on the intensity of the serologic response following the third vaccination dose. Results Thirty-six allo-HSCT recipients, with a mean age of 42.42 years and a median time of 133 days between hematopoietic stem cell transplant (allo-HSCT) and the start of vaccination, were analyzed. Our findings, using the generalized estimating equation (GEE) model, indicated that, compared with the baseline ISR of 1.55 [95% confidence interval (CI) 0.94 to 2.17], the ISR increased significantly during the three-dose SARS-CoV-2 vaccination regimen. The ISR reached 2.32 (95% CI 1.84 to 2.79; p = 0.010) after the second dose and 3.87 (95% CI 3.25 to 4.48; p = 0.001) after the third dose of vaccine, reflecting 69.44% and 91.66% seropositivity, respectively. In a multivariate logistic regression analysis, the female sex of the donor [odds ratio (OR) 8.67; p = 0.028] and a higher level donor ISR at allo-HSCT (OR 3.56; p = 0.050) were the two positive predictors of strong immune response following the third vaccine dose. No serious adverse events (i.e., grades 3 and 4) were observed following the vaccination regimen. Conclusions We concluded that early vaccination of allo-HSCT recipients with a three-dose RBD–TT-conjugated SARS-CoV-2 vaccine is safe and could improve the early post-allo-HSCT immune response. We further believe that the pre-allo-HSCT SARS-CoV-2 immunization of donors may enhance post-allo-HSCT seroconversion in allo-HSCT recipients who receive the entire course of the SARS-CoV-2 vaccine during the first year after allo-HSCT.